Implementation Of Regional Regulation No. 3 Of 2022 Regarding Child Friendly District In Langkat District Viewed From The Perspective Of Fiqh Siyasah - Afinzha Masar; Syofiaty Lubis (Unissula, 2023)
Child Friendly District (KLA) is a program that guarantees and protects children's rights so that they can live, grow, develop and participate optimally in accordance with human dignity and dignity and avoid violence and discrimination. In Indonesia, violations of children's rights are increasingly common. Therefore, by enacting local regulations regarding child-friendly districts in Langkat Regency, in this case, the aim is to uphold children's rights. This study describes the implementation of Regional Regulation No. 3 of 2022 concerning KLA through 5 Clusters. There are still unfulfilled children's rights, such as low school participation, inadequate health insurance, limited infrastructure for children, and cases of child abuse. The results of the implementation of the KLA policy experienced obstacles in several factors, to be precise, the number and quality of human resources had to be expanded, correspondence and collaboration between policy implementers had not yet taken root so that the satisfaction of children's freedom was not optimal and furthermore the local community's understanding of KLA still did not exist. The KLA policy is in accordance with the principles of fiqh siyasa because it can provide benefits to people's lives, especially children.